Bullying in the adolescence and anxiety: an integrative review (Revista Lusófona de Educação, 2025)
School bullying is a problem that affects the mental health of students. This study aimed to verify therelationship between adolescents’ involvement in bullying situations and anxiety. An integrative literature review was conducted, consulting four databases. The data were analyzed descriptively, and the methodological quality of the reviewed studies was assessed. The review corpus comprised 15 articles published between 2017 and 2024. Most of the reviewed studies have strong scientific evidence and a low risk of bias. It was found that girls and bullying victims are more vulnerable to developing anxiety disorders. Students who witness aggressive behaviors at school are also affected and have a potential risk of developing anxiety symptoms. The original contribution of the study lies in the particularization of the issue of anxiety in relation to bullying, presenting aspects that can be used in intervention programs aimed at students’ mental health.